Cloud Security System With Sequel Homomorphic Encryption and Diffie-Hellman Algorithm - Kuppuswamy, K; Nagarajan, MR (International Journal of Computer Sciences and Engineering, 2025)
A set of resources and services offered over the Internet, is called cloud computing. These computing services are delivered from data centers located across the world. Cloud computing consumers benefited by providing virtual resources via internet such as Platform, Infrastructure and Software as a Service. The consequential challenge in cloud computing are the privacy and security issues caused by its multi-tenancy nature and the outsourcing of infrastructure, sensitive data. It is available on Pay-Per-Use model. Various malicious activities from illegal users have threatened this technology such as data misuse, inflexible access control mechanism. The occurrence of these threats may result into spoil or illegal access of critical and private data of end user and business user. In this paper, we identify the most vulnerable security issues or attribute in cloud computing architecture, which will enable both end users and vendors to know about the key security threats associated with cloud computing and propose relevant solution directives to strengthen security in the cloud computing environment. We propose secure cloud architecture by using sequel homomorphic encryption scheme with diffie-hellman algorithm for organizations to strengthen the security mechanism